Efficiency enhanced adaptive quasi-sliding mode controller for variable-speed induction motor drive - Jacob, Shaija Palackappillil; Daniel, Asha Elizabeth (Institute of Advanced Engineering and Science, 2025)
Recent advancements in automated manufacturing and processing industries necessitate fast-responding, efficient, and robust methods for controlling induction motor (IM) drives. Classical proportional-integral (PI) controllers provide optimal performance only at specific operating points and are sensitive to parameter variations. This work proposes an adaptive quasi-sliding mode controller (AQSMC), which utilizes a tangent (tanh) function as the switching function and demonstrates enhanced robustness and adaptability across a wider range of operating conditions. The AQSMC employs an adaptation law to estimate the dynamic disturbances, offering insensitivity to structured and unstructured uncertainties. Numerical simulations are carried out with the AQSMC that analytically deduces the optimum field flux ensuring efficient performance. A lookup table derived from the efficiency optimization algorithm (EOA) is incorporated to further streamline the computational requirements. To validate simulation results, a prototype was developed using a 1 HP induction motor, a DSP controller board with a TI C2000 Delfino MCU F28379D microcontroller, and an IGBT-based Inverter module. Simulations show a 6.3% efficiency improvement at half load and 300 rpm, while experimental analysis records a 3.9% improvement with the EOA, highlighting the potential for enhancing energy efficiency in various industrial applications.